1994
DOI: 10.1159/000316237
|View full text |Cite
|
Sign up to set email alerts
|

Brainstem Reticular Nuclei that Project to the Thalamus in Rats: A Retrograde Tracer Study; pp. 32–39

Abstract: The precise nuclear origins of projections from the brainstem reticular formation to the thalamus were identified in rats using two retrograde tracing substances: wheat germ agglutinin-horseradish peroxidase conjugate, and Fluoro-Gold. Injections of these tracers were made into a variety of thalamic nuclei, including the intralaminar nuclei (most of these also involved the lateral part of the mediodorsal nucleus), the central part of the mediodorsal nucleus, the ventrolateral/ ventromedial nuclei, and the vent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 13 publications
3
9
0
Order By: Relevance
“…We also found sparse labelling of somata in several other brain regions, which has implications for the interpretability of our data on thalamic innervation in the embryonic stages. Of these regions we found that mRF cells that project to the thalamus are located more dorsally than where we observed Ntsr1 + cells (Newman and Ginsberg, 2008). Also the hypothalamic Ntsr1 + cells, which in principle could be part of the subset of thalamus-projecting neurons, we conclude that the proportion of RFP + fibers in the VL, VM and Pf nuclei is limited (Vertes et al, 1995;Shimogawa et al, 2015).…”
Section: Technical Considerationssupporting
confidence: 42%
“…We also found sparse labelling of somata in several other brain regions, which has implications for the interpretability of our data on thalamic innervation in the embryonic stages. Of these regions we found that mRF cells that project to the thalamus are located more dorsally than where we observed Ntsr1 + cells (Newman and Ginsberg, 2008). Also the hypothalamic Ntsr1 + cells, which in principle could be part of the subset of thalamus-projecting neurons, we conclude that the proportion of RFP + fibers in the VL, VM and Pf nuclei is limited (Vertes et al, 1995;Shimogawa et al, 2015).…”
Section: Technical Considerationssupporting
confidence: 42%
“…The classical reticular nuclei that are severely affected in AD include the nucleus cuneiforme, the deep mesencephalic nucleus, the noncholinergic portion of the pedunculopontine tegmental nucleus, and the nucleus pontis oralis. These nuclei presumably send glutamatergic ascending projections to the basal ganglia and intralaminar thalamic nuclei, which project “diffusely” to various cortical regions 49, 50. These projections are thought to be crucial for the activation of the cerebral cortex, necessary for the maintenance of consciousness.…”
Section: Discussionmentioning
confidence: 99%
“…Paxinos (Paxinos and Watson, 1986;Paxinos and Huang, 1995) considers this area an extension of nucleus reticularis pontis oralis and describes a separate pedunculopontine tegmental nucleus. On the basis of thalamoreticular connections, Newman now agrees that at least part of nucleus reticularis pedunculopontinus (pars dissipatus) may be a rostral extension of nucleus reticularis pontis oralis pars medialis (Newman and Ginsberg, 1994).…”
Section: Mesencephalic Reticular Formationmentioning
confidence: 91%